2021
DOI: 10.3897/zookeys.1078.75461
|View full text |Cite
|
Sign up to set email alerts
|

Description of a new species of the genus Neopseustis Meyrick, 1909 from China, with a new classification of the genus (Lepidoptera, Neopseustoidea, Neopseustidae)

Abstract: A new species of the genus Neopseustis Meyrick, 1909, Neopseustis chentangensis S.Y. Huang & Chen sp. nov., which was confirmed by both morphological and molecular methods, is described from Xizang, China. This is currently the westernmost species in Asia of the primitive lepidopteran family Neopseustidae. The new species is externally reminiscent of N. moxiensis Chen & Owada, 2009; however, it can be easily distinguished from the latter by comparison of the male genitalia and is further distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Davis (1975) considered Neopseustis is divided into two groups: one is characterized principally by the well-developed, densely pubescent parameres, and the other one is characterized by the poorly developed and naked parameres. Huang et al (2021) consider that this genus may actually comprise of at least four groupsafter utilizing more data from previously unsampled taxa. However, in the present study, N. archiphenax, N. rectagnatha, N. meyricki and N. sinensis belong to one group is suggested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Davis (1975) considered Neopseustis is divided into two groups: one is characterized principally by the well-developed, densely pubescent parameres, and the other one is characterized by the poorly developed and naked parameres. Huang et al (2021) consider that this genus may actually comprise of at least four groupsafter utilizing more data from previously unsampled taxa. However, in the present study, N. archiphenax, N. rectagnatha, N. meyricki and N. sinensis belong to one group is suggested.…”
Section: Discussionmentioning
confidence: 99%
“…The family Neopseustidae is an archaic lepidopteran group which consists of 4 genera and 14 species, and distributed in Southeast Asia and South America (Davis 1975;Davis & Nielsen 1980, 1985Chen et al 2009;Liao et al 2021;Huang et al 2021). Two genera and eight species have been recorded from mainland China (Chen et al 2009;Liao et al 2021;Huang et al 2021), but no species has been reported from Chongqing Municipality. The insect inventories organized by Prof. Zhi-Sheng Zhang of Southwest University were constructed in Yintiaoling Nature Reserve, Chongqing of China.…”
Section: Introductionmentioning
confidence: 99%